A simplified model of flexible power point tracking algorithms in double-stage photovoltaic systems - Utrilla, Candelaria (2023)
Traditionally, photovoltaic (PV) systems have been operated using maximum power point tracking algorithms, which force the PV arrays to produce the maximum available power at all times. Nevertheless, distribution system operators are increasingly asking for flexible power point tracking (FPPT) algorithms, which allow the regulation of the PV power to a predefined reference value. FPPTs are difficult to tune and often have non-linear behavior. It complicates the modeling of PV systems for power system stability studies. This paper proposes a simplified model that reproduces the dc-side dynamics of a double-stage FPPT-controlled PV system. In addition to its simple tuning, the key advantage of the proposed model is that it can be easily translated into differential equations, which can be used in stability analyses. The proposed model is validated on a temporal simulation as well as a small-signal stability study.